Comparison of Transoral vs. Extraoral Approach in Subcondylar Fracture Fixation - Muhammad Hamza Hashim, Usman ul Haq, Zainab Khalid, Amna Hassan, Yumna Shafqat Baig, Rubab Mumtaz (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This experimental study aimed to compare the efficacy and outcomes of transoral and extraoral approaches in the fixation of mandibular subcondylar fractures. A total of 60 patients with isolated,displaced subcondylar fractures were randomly assigned to two groups: Group A underwent fixation via the transoral approach, while Group B received fixation through the extraoral approach